Re‐investigation of the fragmentation of protonated carotenoids by electrospray ionization and nanospray tandem mass spectrometry. (9th June 2016) - Neto, Fausto Carnevale; Guaratini, Thais; Costa‐Lotufo, Letícia; Colepicolo, Pio; Gates, Paul J.; Lopes, Norberto Peporine
Abstract : Rationale: Carotenoids are polyene isoprenoids with an important role in photosynthesis and photoprotection. Their characterization in biological matrices is a crucial subject for biochemical research. In this work we report the full fragmentation of 16 polyenes (carotenes and xanthophylls) by electrospray ionization tandem mass spectrometry (ESI‐CID‐MS/MS) and nanospray tandem mass spectrometry (nanoESI‐CID‐MS/MS). Methods: Analyses were carried out on a quadrupole time‐of‐flight (QTOF) mass spectrometer coupled with a nanoESI source and on a Fourier transform ion cyclotron resonance (FTICR) mass spectrometer with an ESI source. The formulae of the product ions were determined by accurate‐mass measurements. Results: It is demonstrated that the fragmentation routes observed for the protonated carotenoids derive essentially from charge‐remote fragmentations and pericyclic rearrangements, such as electrocyclic and retro‐ene eliminations (assisted or not by a sigmatropic hydrogen shift). All mechanisms are dependent on cis‐trans isomerization through the formation of several conjugated polyene carbocation intermediates. Some specific ions for the carotenoid epoxides were justified through formation of cyclic oxonium ions. Conclusions: Complete fragmentation pathways of protonated carotenoids by ESI‐ and nanoESI‐CID‐MS/MS provided structural information about functional groups, polyene chain and double bonds, and contribute to identification of carotenoids based on MS/MS fragmentation patterns. Copyright © 2016 John Wiley & Sons, Ltd.